We're for Smoke : Outlaws and Outliers of Panther City - Nobles, Mark A., 1960- (Book collections on Project MUSE., 2021)
"From Hell's Half Acre to Quality Grove, We're for Smoke tells the wild and woolly story of turn-of-the-century Fort Worth, a cow town on the cusp of becoming a modern industrial city. Told through a series of fictionalized characters drawn from actual newspaper accounts detailing their tangles with the law, ranging from high and low society, black and white, male and female, perpetrator and victim, We're for Smoke reveals a society scrabbling to emerge from the chaotic growing pains of the frontier West. The book reproduces actual turn-of-the-century newspaper accounts of gunfights, jailbreaks, attempted lynchings, and riots. Readers and fans of The Son by Philipp Meyer, Boardwalk Empire by Nelson Johnson, and Larry McMurtry's Horseman Pass By would enjoy We're for Smoke"--